Failure analysis method for the presizing of multi-rotors eVTOL - Basset, P.M.; Perret, R. (My University, 2022)
The new kind of aircraft electric Vertical Take-Off and Landing (eVTOL) concepts are well suited for the Advanced Air Mobility including Urban Air Mobility. The new paradigm of design for these Advanced Aircraft no longer relies on autorotation capability, but on redundancy. Redundancy is one required condition, but it may not be enough to ensure a safe controlled flight in case of failure of one or more thrust generator systems, i.e. {energy system – controller - motor – propeller}. This paper focuses on the crucial issue of setting a methodology to assess if an eVTOL configuration is able to cope with one or more thrust generator failure(s). This is a crucial step for their predesign because the thrust generators must be sized to withstand the most demanding conditions, which are imposed by the worst critical failure cases. Therefore, the analysis of the different failure cases is needed before the sizing of the rotors and more generally of the thrust generator system. A numerical method is presented as well as results giving a comprehensive overview for the axi-symmetrical circular multi-rotors configurations with or without coaxial rotors and more generally for eVTOL with all rotors thrusting always in the same unique direction.